Transformation of Intellectual Property Rights Protection in the Blockchain Era: Exploring the Potential of Revolution or Evolution in the Management of Innovation and Creativity - Candra Yoga, I Komang Gede Bisma; Laksmi Dewi, Cokorde Istri Dian (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Blockchain technology has become the center of attention in an effort to maintain sustainable economic growth in the digital era by strengthening the protection of intellectual property rights (IPR). In this article, we explore the impact of blockchain on IPR transformation and its potential to improve the protection of future innovations. By investigating the advantages and challenges involved, we present insights into how blockchain can strengthen the security, transparency, and authentication of IPR. However, challenges such as regulatory compatibility and data security also need to be addressed. Through collaboration between various parties, blockchain can be a powerful tool to create an ecosystem that supports the growth of innovation and creativity in the digital era. The purpose of this research is to explore the role of blockchain in the transformation of intellectual property rights (IPR) protection and its potential impact on future innovation. The results of the discussion show that blockchain has great potential to improve the security, transparency, and authentication of IPR, but it also faces challenges such as regulatory compatibility and data security that need to be addressed